On the Geometry of Holomorphic Developable Vector Fields on Almost Hermitian Manifolds - Kirichenko, V. F.; Kuzakon’, V. M. (Ukrains’kyi Matematychnyi Zhurnal, 2013)
The determination of conditions for the invariance of geometric objects under the action of a group of transformations is one of the most important problems of geometric research. We study the invariance conditions for almost Hermitian structures relative to the action of a local one-parameter group of diffeomorphisms generated by a developable vector field on a manifold. Moreover, we investigate the relationship between developable (in particular, concircular) vector fields on Riemannian manifolds and locally concircular transformations of the metric of these manifolds.